2003
DOI: 10.1167/3.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Timecourse of neural signatures of object recognition

Abstract: How long does it take for the human visual system to recognize objects? This issue is important for understanding visual cortical function as it places constraints on models of the information processing underlying recognition. We designed a series of event-related potential (ERP) experiments to measure the timecourse of electrophysiological correlates of object recognition. We find two distinct types of components in the ERP recorded during categorization of natural images. One is an early presentation-locked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
160
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(182 citation statements)
references
References 37 publications
(47 reference statements)
21
160
1
Order By: Relevance
“…The modulation of the frontal and posterior N100 response to artifacts is consistent with previous studies that compared the effect of animals and artifacts in visual categorization (Antal et al, 2000(Antal et al, , 2001Proverbio et al, 2007). Furthermore, our posterior N100, peaking around 200 ms, resembles the negative deflection over occipito-temporal areas (N200 or N150) reflecting selective attention effects in target decision tasks using animals (Codispoti et al, 2006;Johnson and Olshausen, 2003) and objects (Van Rullen and Thorpe, 2001). The N150 has been considered to reflect perceptual selection mechanisms devoted to high level features extraction (as those selected in visual categorization) (Codispoti et al, 2006) and, more importantly, it has been demonstrated not to be dependent on low level sensory analysis (Van Rullen and Thorpe, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…The modulation of the frontal and posterior N100 response to artifacts is consistent with previous studies that compared the effect of animals and artifacts in visual categorization (Antal et al, 2000(Antal et al, , 2001Proverbio et al, 2007). Furthermore, our posterior N100, peaking around 200 ms, resembles the negative deflection over occipito-temporal areas (N200 or N150) reflecting selective attention effects in target decision tasks using animals (Codispoti et al, 2006;Johnson and Olshausen, 2003) and objects (Van Rullen and Thorpe, 2001). The N150 has been considered to reflect perceptual selection mechanisms devoted to high level features extraction (as those selected in visual categorization) (Codispoti et al, 2006) and, more importantly, it has been demonstrated not to be dependent on low level sensory analysis (Van Rullen and Thorpe, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…This difference in length could have resulted in a harder task -our participants took longer to respond to symbols, while in Araújo et al no stimulus type effect was observed on RTs -and therefore in a larger N1 component. This suggests a greater perceptual resource allocation for symbols than for letter strings, and is consistent with the fact that the N1 component is an index of perceptual processing: Increased visual processing demands are reflected by more negative values (e.g., Johnson & Olshausen, 2003;Kiefer, 2001;Tanaka, Luu, Weisbrod, & Kiefer, 1999). Yet, visual inspection of Fig.…”
Section: Discussionsupporting
confidence: 73%
“…This could be in the form that first there is a fast and unconscious feedforward sweep that is followed by more in-depth recurrent processing, only the latter leading to conscious perception (Lamme 2003). This is consistent with findings by Johnson and Olshausen (2003), who report two ERP signals related to object recognition, an early presentation-locked one, and a later signal that correlates in timing with the response times for recognition.…”
Section: Experimental Evidencesupporting
confidence: 89%